2018
DOI: 10.1111/jeb.13231
|View full text |Cite
|
Sign up to set email alerts
|

Temperature fluctuations during development reduce male fitness and may limit adaptive potential in tropical rainforest Drosophila

Abstract: Understanding the potential for organisms to tolerate thermal stress through physiological or evolutionary responses is crucial given rapid climate change. Although climate models predict increases in both temperature mean and variance, such tolerances are typically assessed under constant conditions. We tested the effects of temperature variability during development on male fitness in the rainforest fly Drosophila birchii, by simulating thermal variation typical of the warm and cool margins of its elevationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…In the neotropical pseudoscorpion, males produced 45% less sperm at temperatures mimicking 3.5 ∘ C of warming (Zeh et al, 2012). The temperature sensitivity of male sperm and the extent to which species can shift male sterility remains a poorly understood phenomenon (David et al, 2005;Zeh et al, 2012;Saxon et al, 2018). Thermal sensitivities may also differ across life stages (Sinclair et al, 2016;Zhao et al, 2017) and Kingsolver et al (2011) have shown that larvae and pupae of Manduca sexta have different thermal sensitivities and differ in their TPC.…”
Section: Upper Thermal Limits: Acute and Fitness-basedmentioning
confidence: 99%
“…In the neotropical pseudoscorpion, males produced 45% less sperm at temperatures mimicking 3.5 ∘ C of warming (Zeh et al, 2012). The temperature sensitivity of male sperm and the extent to which species can shift male sterility remains a poorly understood phenomenon (David et al, 2005;Zeh et al, 2012;Saxon et al, 2018). Thermal sensitivities may also differ across life stages (Sinclair et al, 2016;Zhao et al, 2017) and Kingsolver et al (2011) have shown that larvae and pupae of Manduca sexta have different thermal sensitivities and differ in their TPC.…”
Section: Upper Thermal Limits: Acute and Fitness-basedmentioning
confidence: 99%
“…Twelve picture-winged Drosophila species are currently listed as endangered or threatened, and monitoring over the last 30 years has documented sharp declines and reduced distributions for many of the nonlisted species (Richardson, 2006). These Drosophila, like many tropical ectotherms, are thought to be particularly vulnerable to climatic changes due to their narrow physiological tolerance windows (Saxon, O'Brien, & Bridle, 2018), as well as limited habitat ranges and highly specific native host plant associations (Magnacca, Foote, & O'Grady, 2008;Magnacca & Price, 2015).…”
mentioning
confidence: 99%
“…Mean global temperatures, thermal variability, and the frequency of extreme environmental events have increased, and these have had significant impacts on biodiversity (Dawson, Jackson, House, Prentice, & Mace, ; Gitay, Suárez, Watson, & Dokken, ; Meehl & Tebaldi, ; Pachauri & Reisinger, ; Palmer et al, ; Vázquez, Gianoli, Morris, & Bozinovic, ). These changes in the thermal environment are expected to be particularly challenging for ectotherms because their physiology is directly dependent on ambient temperatures (Pörtner, ; Saxon, O'Brien, & Bridle, ; Sunday, Bates, & Dulvy, ). To a large extent the susceptibility and vulnerability of ectotherms to climate change has been assessed through the study of thermal performance curves (TPCs) which characterize the relationship between performance or fitness and body temperature (Sinclair et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These changes in the thermal environment are expected to be particularly challenging for ectotherms because their physiology is directly dependent on ambient temperatures (Pörtner, 2002;Saxon, O'Brien, & Bridle, 2018;Sunday, Bates, & Dulvy, 2011). To a large extent the susceptibility and vulnerability of ectotherms to climate change has been assessed through the study of thermal performance curves (TPCs) which characterize the relationship between performance or fitness and body temperature (Sinclair et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation